Simultaneous quantification of Myelin Basic Protein and Tau proteins in cerebrospinal fluid and serum of Multiple Sclerosis patients using nanoimmunosensor - Derkus, Burak; Bozkurt, Pinar Acar; Tulu, Metin; Emregul, Kaan C.; Yucesan, Canan; Emregul, Emel (ELSEVIER ADVANCED TECHNOLOGY, 2017)
This study was aimed at the development of an immunosensor for the simultaneous quantification of Myelin Basic Protein (MBP) and Tau proteins in cerebrospinal fluid (CSF) and serum, obtained from Multiple Sclerosis (MS) patients. The newly developed GO/pPG/anti-MBP/anti-Tau nanoimmunosensor has been established by immobilization of MBP and Tau antibodies. The newly developed nanoimmunosensor was tested, optimized and characterized using differential pulse voltammetry (DPV) and electrochemical impedance spectroscopy (EIS). The developed nanoimmunosensor was seen to have detection limits of 0.30 nM for MBP and 0.15 nM for Tau proteins which were sufficient for the levels to be analysed in neuro-clinic. The clinical study performed using CSF and serum of MS patients showed that the designed nanoimmunosensor was capable of detecting the proteins properly, that were essentially proven by ELISA.
Keywords: Myelin Basic Protein; Tau; Multiple Sclerosis; Immunosensor; Dendrimer; Graphene oxide; Electrochemical impedance spectroscopy; Differential pulse voltammetry; ALZHEIMERS-DISEASE; MASS-SPECTROMETRY; Biophysics; Biotechnology & Applied Microbiology; Chemistry; Electrochemistry; Science & Technology - Other Topics